PENGARUH MODEL PEMBELAJARAN COOPERATIVE SCRIPT BERBANTUAN MEDIA GAMBAR FLASHCARD TERHADAP KEMAMPUAN PEMAHAMAN KONSEP IPA SISWA KELAS IV SD - Astuti, Rini; Suryani, Ela (JURNAL PENDIDIKAN DASAR NUSANTARA, 2022)
This study aims to determine the effect of the Cooperative Script learning model with the help of Flahcard Image Media on the Concept Understanding of Class IV Students. This type of research is an experiment with a nonequivalent control group design. The population in this study were students of SD N Jetis 01 and students of SD N Jetis 03 who were still in one cluster, then for the sample in this study were grade 4 students at SD N Jetis 01 and grade 4 students at SD N Jetis 03. Data collection instruments using observation, questionnaires, interviews, tests, and documentation. The data analysis technique was normality test, homogeneity test, independent sample t test and simple linear regression test. The results of the research show: (1) There are differences in the use of the Cooperative Script model assisted by flashcard image media for the experimental class and the Cooperative Script model only for the control class on the ability to understand concepts of fourth grade students, as evidenced by the significance level of 0.001 < 0.05 using the independent sample t test. Test (2) There is an effect of using the Cooperative Script model with the help of Flahcard Image Media on the Concept Understanding of Class IV Students, as evidenced by a significance level of 0.000 <0.05 using a simple linear regression test. The results of this study can be concluded that the Cooperative Script learning model assisted by Flahcard Image Media has an effect on increasing students’ understanding of concepts.